Customer incivility and frontline employees' revenge intentions: interaction effects of employee empowerment and turnover intentions. Issue 4 (18th May 2020) - Bani-Melhem, Shaker; Quratulain, Samina; Al-Hawari, Mohd Ahmad
ABSTRACT: Drawing on reciprocity, revenge, and retaliation theories, we examined a three-way interaction effect of customer incivility, turnover intentions and employee empowerment on the revenge intentions of frontline employees (FLEs) in the UAE service organizations. We tested the hypotheses using data from two different studies through a time-lagged research design. In Study 1, a sample of 192 FLEs working in a variety of service organizations (including those operating in hospitality sector) was collected. Study 2 replicated the findings of study 1 by collecting a sample of 184 FLEs working in hospitality organizations. The results of both studies consistently show that the strongest negative reaction (revenge intention) in response to customer incivility is displayed by highly empowered employees when they have high turnover intentions. Based on our novel findings, hospitality and other service-oriented organizations need to understand that interaction of situational factors with episodes of customer incivility can prompt stronger employee reactions.